Are Commodity Prices Driven by Fundamentals?. (21st January 2013) - De Meo, Emanuele
Abstract : Physical scarcity is hardly sufficient to explain commodity price swings. However, despite of clues of commodity market inefficiency in the last decade, excess volatility in commodity markets emerges only under strong assumptions. When we allow for non‐stationarity in commodity prices and time variation in commodity‐specific risk premia, evidence of commodity market inefficiency becomes significantly weaker. Moreover, there is some evidence of commodity‐specific regime changes in commodity markets, with negligible or even positive correlation between efficiency and market liquidity.